Isolated renal mucormycosis: a rarity - Sandhu, Arjun S.; Jha, Aditya A. (International Surgery Journal, 2020)
Mucormycosis is a rare, opportunistic, highly aggressive, fungal infection primarily noted in immunocompromised individuals. Isolated involvement of any organ is rare in general. Isolated renal involvement is unusual, with only a few cases reported in literature to date. We present a rare case of isolated renal mucormycosis successfully managed with systemic anti-fungal therapy and nephron sparing surgery.